An untargeted metabolomic insight into the high-pressure stress effect on the germination of wholegrain Oryza sativa L. (February 2021) - Ruan, Yifan; Cai, Zhendong; Deng, Yun; Pan, Daodong; Zhou, Changyu; Cao, Jinxuan; Chen, Xiaojia; Xia, Qiang
Graphical abstract: Highlights: A metabolomic insight into high-pressure (HP)-assisted germination was provided. Brown rice (BR) metabolome supported the results of targeted quality analysis. HP stress caused the reprogramming of metabolic pathways during BR germination. HP stress inhibited the biotransformation of phenolic acids during germination. GABA shunt pathway was enhanced by HP stress due to the shift of metabolic flow. Abstract: High hydrostatic pressure (HHP) technique is used as a novel abiotic stress factor for efficiently enhancing the biosynthesis of selected bioactive phytochemicals in germinated wholegrain, but the information about HHP stress-induced metabolic changes remains rather limited. Thus, the current work employed an untargeted gas chromatography-mass spectrometry-based metabolomic approach combining with multivariate models to analyze the effect of mild HHP stress (30 MPa/5 min) on the overall metabolome shifts of wholegrain brown rice (WBR) during germination. Simultaneously, major phenolics in germinated WBR (GBR) were detected by ultra-performance liquid chromatography/quadrupole time-of-flight mass spectrometry, to explore the potential relationship between HHP stress-induced rice metabolome alternations and the biotransformation of bioactive components. The results demonstrated that the influence of HHP stress on GBR metabolite profiles was defined by germination durations, as revealed by the differentiation of the stressed grains from the naturally germinated grains at different germination points according to principal component analysis. This was further confirmed by the results of orthogonal projections to latent structures discriminant analysis, in which the discriminating metabolites between naturally germinated and HHP-stressed grains varied across the germination process. The metabolite signatures differentiating natural and HHP-stressed germination included glycerol-3-phosphate, monosaccharides, gamma-aminobutyric acid, 2, 3-butanediol, glyceryl-glycoside, amino acids and myo-inositol. Besides, HHP stress led to the increase in ribose, arabinitol, salicylic acid, azelaic acid and gamma-aminobutyric acid, as well as the reduced phenolic acids. These results demonstrated that HHP stress before germination matched with appropriate process parameters could be used as a promising technology to tailor metabolic features of germinated products, thus exerting targeted nutrition and health implications.